Studi Literasi Tersistematis Implementasi Metode-Metode Pengembangan Sistem Informasi Berbasis Basis Data Terdistribusi - Endang Lestariningsih; Rara Sriartati Redjeki; Edy Supriyanto; Hari Murti; Eka Ardhianto; Eko Nur Wahyudi; Widiyanto Tri Handoko (Universitas Wahid Hasyim, 2024)
Information systems cannot be separated from a database as the main database. As time goes by, the amount of data processed by information systems increases significantly. Currently, databases are not only stored in one storage media location, but can also be stored in different locations and locations. This is also supported by advances in network technology, both hardware and supporting software. The distributed database system model provides significant support for processing data stored in different locations. Many information system implementations use the concept of a distributed database system. The aim of this research is to study the development of database system implementation using distributed database system technology. This research uses a systematic literature observation approach. The results obtained are that the concept of a distributed database system is still used today to support information system governance that produces information tailored to user objectives. Systems created using development techniques based on the distributed database concept have advantages in several aspects of development.